2015
DOI: 10.3748/wjg.v21.i35.10057
|View full text |Cite
|
Sign up to set email alerts
|

Stool DNA methylation assays in colorectal cancer screening

Abstract: Colorectal cancer (CRC) is fourth most common cancer in men and third in women worldwide. Developing a diagnostic panel of sensitive and specific biomarkers for the early detection of CRC is recognised as to be crucial for early initial diagnosis, which in turn leads to better long term survival. Most of the research on novel potential CRC biomarkers in the last 2 decades has been focussed on stool DNA analysis. In this paper, we describe the recent advances in non-invasive CRC screening and more specifically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…Another CRC screening technique is stool-based analysis of abnormal DNA modifications, such as DNA mutation and methylation, as these alterations have an essential role in tumor formation. [9][10][11][12] Cologuard Ò (Exact Sciences Corporation, Madison, WI, United States) is a US FDA approved multitarget stool DNA test, which includes molecular assays for the detection of aberrantly methylated and mutated genes. As Imperiale et al showed in their recent work, the test has higher sensitivity for finding CRC in comparison to FIT; however, the detection of adenoma patients is less effective.…”
Section: Introductionmentioning
confidence: 99%
“…Another CRC screening technique is stool-based analysis of abnormal DNA modifications, such as DNA mutation and methylation, as these alterations have an essential role in tumor formation. [9][10][11][12] Cologuard Ò (Exact Sciences Corporation, Madison, WI, United States) is a US FDA approved multitarget stool DNA test, which includes molecular assays for the detection of aberrantly methylated and mutated genes. As Imperiale et al showed in their recent work, the test has higher sensitivity for finding CRC in comparison to FIT; however, the detection of adenoma patients is less effective.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed that DNA cytosine modifications serve an important role in cancer biology, and provide promising biomarkers for cancer diagnosis and prognosis evaluation (10,34). Several epigenetic biomarkers have been studied for the diagnosis of CRC, including SEPT9 (35), BMP3, NDRG4 (36) and hMLH1 (37). The ROC curves generated in the current study demonstrated that EED hypomethylation is a good biomarker for the diagnosis of CR.…”
Section: Discussionmentioning
confidence: 54%
“…This is a result of the copious amounts of DNA shed from the tumour cells from the thoracic and oral regions into sputum and saliva. Stool can also be used to detect tumour-derived methylated DNA biomarkers for colorectal cancer [ 34 36 ] and pancreatic cancer [ 37 ]. A large proportion of the sample types evaluated to detect circulating cell-free biomarkers are blood based [ 38 , 39 ] in the detection of many cancers [ 40 , 41 ] as it contains a high volume of genetic material.…”
Section: Types Of Noninvasive Epigenetic Biomarkersmentioning
confidence: 99%